5-hydroxymethylcytosines from circulating cell-free DNA as noninvasive prognostic markers for gastric cancer - Yingli Fu; Donghui Cao; Yanhua Wu; Zhifang Jia; Yangyu Zhang; Chenhao Fu; Xueyuan Cao; Jing Jiang (PLoS ONE, 2025)
Background Prognostic assessment plays a crucial role in guiding clinical management and treatment decisions for gastric cancer patients. The enrichment characteristics of 5-hydroxymethylcytosine (5hmC) in circulating cell-free DNA (cfDNA) has emerged as potential prognostic epigenetic markers. Methods Using 5hmC-Seal combined with next-generation sequencing (NGS), we profiled the genome-wide distribution of 5hmC in plasma cfDNA samples from 51 gastric cancer patients. Prognostic biomarkers were selected via random survival forest and Cox proportion hazards models, and a prognostic model was subsequently constructed. Results Seven prognostic biomarker genes were identified, and the 7-gene prognostic model demonstrated a concordance index (C-index) of 0.892 (95% CI = 0.786–0.998). Patients in the high risk group had a significantly worse overall survival (OS) than those in low-risk group (log-rank P = 0.00012). When the cfDNA 5hmC risk-score was integrated with the traditional clinical characteristics, the C-index increased from 0.819 (95% CI = 0.727–0.911) to 0.904 (95% CI = 0.853–0.955). Multivariate analysis adjusted for age, TNM stage, and chemotherapy confirmed that a high risk-score of cfDNA 5hmC model was an independent predictor of poor OS (hazard ratio [HR]=27.47, 95% CI = 3.28–230.25). Conclusion cfDNA 5hmC serves as an effective prognostic biomarker with high predictive value for the long-term survival in postoperative gastric cancer patients.